Selecting groundnut varieties for crop-livestock systems? do not forget the farmers' cattle! - Larbi, Asamoah; Olorunju, P.E.; Dung, D.D.; Etela, I. (1998)
This paper discusses why c rop residues are important for the farmer, how dual-purpose groundnut varieties can make a difference in the smallholder farming system; a multidisciplinary approach to investigate the agronomic aspects of dual-purpose groundnut varieties as well as the complementary aspects of animal nutrition and socio-economics; the search for dual-purpose varieties, and testing farmer preferences for dual-purpose varieties. Variations in fodder and seed yields and leaf: stem ratio; relationships between seed and fodder yields; liveweight gain of West African Dwarf sheep fed fodder from three late-maturing groundnut varieties, and groupings of 38 late-maturing groundnut cultivars into high, medium, and low potential groups for fodder and seed production and presented in tabular form.